GROWING ORAL SPEECH THROUGH THE FORMATION OF CREATIVE THINKING OF PRIMARY SCHOOL STUDENTS (Web of Teachers: Inderscience Research, 2024)
This article discusses how to develop students' creative thinking in their native language and reading literacy classes in primary education through speech development activities.